2014
DOI: 10.5229/jecst.2014.5.2.37
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid-based Electrolytes for Li Metal/Air Batteries: A Review of Materials and the New 'LABOHR' Flow Cell Concept

Abstract: The Li-O 2 battery has been attracting much attention recently, due to its very high theoretical capacity compared with Li-ion chemistries. Nevertheless, several studies within the last few years revealed that Li-ion derived electrolytes based on alkyl carbonate solvents, which have been commonly used in the last 27 years, are irreversibly consumed at the O 2 electrode. Accordingly, more stable electrolytes are required capable to operate with both the Li metal anode and the O 2 cathode. Thus, due to their fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Subsequently, a variety of IL-based electrolytes (e.g., pyrrolidium and ammonium-based electrolytes) were developed for secondary Li−O2 cells. 337 Nevertheless, the chemical stability of ILs is still under debate. On the found that the pseudo-first-order reaction constant of 1-butyl-1-methylpyrrolidinium bis (trifluoromethylsulfonyl)imide (Pyr14TFSI) with O2 − is at least 3 orders of magnitude lower than that of propylene carbonate (PC).…”
Section: The Important Analogous Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a variety of IL-based electrolytes (e.g., pyrrolidium and ammonium-based electrolytes) were developed for secondary Li−O2 cells. 337 Nevertheless, the chemical stability of ILs is still under debate. On the found that the pseudo-first-order reaction constant of 1-butyl-1-methylpyrrolidinium bis (trifluoromethylsulfonyl)imide (Pyr14TFSI) with O2 − is at least 3 orders of magnitude lower than that of propylene carbonate (PC).…”
Section: The Important Analogous Systemsmentioning
confidence: 99%
“…These make ILs excellent solvents for the lithium–air batteries operated under ambient conditions. Subsequently, a variety of IL-based electrolytes (e.g., pyrrolidium and ammonium-based electrolytes) were developed for secondary Li–O 2 cells . Nevertheless, the chemical stability of ILs is still under debate.…”
Section: Current Statusmentioning
confidence: 99%
“…27 On the other hand pyrrolidinium and piperidinium based cations combined with the bis(trifluoromethanesulfonyl)imide (TFSI) anion have been reported to be functional. [28][29][30] Bresser et al 31 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3 cathode as reported by Monaco et al 20 They used N-butyl-N-methyl-pyrrolidinium TFSI doped with Here, we investigate the rechargeability of a Li-O 2 cell using IL based electrolytes based on five different cations and two different anions as shown in Figure 1. The main focus is N-methyl-N-alkylpyrrolidinium (P 13 and P 14 ) and N-methyl-N-alkyl-pipiridinium (PP 13 ) based cations in combination with the TFSI anion, as these ILs have shown promising results as stable electrolytes in Li-O 2 batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) are salt compounds that remain liquid at or near room temperature (e.g., <100 °C). They have promising industrial applications in lubrication, catalysis, CO 2 capture, , and energy storage. In particular, ILs are considered as promising solvents because of their unique physical and chemical properties compared with traditional organic solvents, including low vapor pressure, good chemical and thermal stability, and potential recyclability. ,, Moreover, countless combinations of cations and anions make it possible to design and optimize ILs with desired properties. To do so, however, requires a fundamental understanding of structure–property relationships in various ILs systems, especially under in situ and operando conditions.…”
mentioning
confidence: 99%